1999
DOI: 10.1890/0012-9658(1999)080[0857:casspc]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Competition Among Secondary-Successional Pine Communities: A Field Study of Effects and Responses

Abstract: Three common associates on secondary-successional pine sites (Andropogon virginicus, Liquidambar styraciflua, and Pinus taeda) were established in a field study in which a wide array of plant densities and species proportions were established using an additive series design. To mimic a specific competitive scenario (i.e., a managed earlysuccessional Pinus stand), Andropogon and Liquidambar were established a year prior to the establishment of Pinus. Competitive effect (the attenuation of resources) and competi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 48 publications
3
12
0
Order By: Relevance
“…The lack of a correspondence between the influence of competitor density on jack pine E or WUE, and the low and often insignificant correlations between jack pine P n and water availability suggested that competition for water was not as important as that for N or light (Shropshire 1999) in our study. Competition for light and water were more apparent in a similar study (Mitchell et al 1999), as seen in growth and physiological response of loblolly pine to light attenuation and water availability in the Upper Coastal Plain of Alabama. Mitchell et al (1999) observed a significant decrease in available soil water throughout the growing season, a phenomenon not observed in our study.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…The lack of a correspondence between the influence of competitor density on jack pine E or WUE, and the low and often insignificant correlations between jack pine P n and water availability suggested that competition for water was not as important as that for N or light (Shropshire 1999) in our study. Competition for light and water were more apparent in a similar study (Mitchell et al 1999), as seen in growth and physiological response of loblolly pine to light attenuation and water availability in the Upper Coastal Plain of Alabama. Mitchell et al (1999) observed a significant decrease in available soil water throughout the growing season, a phenomenon not observed in our study.…”
Section: Discussionsupporting
confidence: 58%
“…Competition for light and water were more apparent in a similar study (Mitchell et al 1999), as seen in growth and physiological response of loblolly pine to light attenuation and water availability in the Upper Coastal Plain of Alabama. Mitchell et al (1999) observed a significant decrease in available soil water throughout the growing season, a phenomenon not observed in our study. We concur with Mitchell et al (1999) that competitive effect and response are important to understand mechanisms regulating competitive interactions when spatiotemporal resource heterogeneity is considered.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Both herbaceous and woody competition threaten survival of planted oak seedlings, with herbaceous competition posing the greatest risk during the first years of establishment [10,11]. Greater impact of herbaceous competition is likely the result of increased exploitation of soil moisture and nutrients due to the more extensive nature of herbaceous species root systems [12].…”
Section: Introductionmentioning
confidence: 99%